Collusion Indicators in the GameStop Short Squeeze - Campbell, Michael J. (Journal of Mathematical Economics and Finance; Vol 9 No 2 (2023): JMEF, Volume IX, Issue 2(17), Winter 2023, 2023)
A new theory and model of the stock market that incorporates decision noise in the spirit of behavioral economics, collaboration in the spirit of experimental economics, and financial data and features in the spirit of econophysics is used to support a theory from 2005 that stock-market collusion should lower the level of stock-market decision noise - i.e., a quantitative way of seeing how traders influence each other in a stock market. This idea is used to find two rare indicators of the GameStop short squeeze – one of which occurred six days before the rapid price increase, which could have potentially reduced the over $19 billion in losses of short sellers by a significant amount. The relationship predicted by the model between temperature and aggregate volume has been validated by data from the GameStop short squeeze.